Jammed Up : Bad Cops, Police Misconduct, and the New York City Police Department - Kane, Robert J. (Book collections on Project MUSE., 2013)
'Jammed Up' is a definitive study of the nature and causes of police misconduct. The authors examines the cases of more than 1500 NYPD officers over a 20 year period that includes a fairly complete cycle of scandal and reform, in the largest, most visible police department in the United States.